Out-of-band conducted susceptibility measurement and analysis of VHF/FM communication system - Fan, Shi Zhao (2013)
With proper frequency management, one can prevent in-band radio frequency interference (RFI). However, at out-of-band (OOB) frequencies, RFI is almost impossible to prevent. And such OOB interference characteristics of communication devices may not be provided by the supplier of the devices. In this paper, we present the results of OOB conducted susceptibility measurement for a VHF/FM communication system. Detailed analysis were given for several of the interference frequencies and lastly, the results were compared with Mil-Std 461C CS04 limit line.